Quantitative Risk Assessment of Ammonia Release from Storage Tanks Using RISKCURVES Software - Alimatun Nashira; Anindita Putri Nugrahani; Anisa Ur Rahmah; Teguh Cahyono (Engineering Proceedings)
Ammonia is a gas with high toxicity, which is produced in large amounts as raw materials for nitrogen-based fertilizer. Fertilizer plants in Indonesia are sometimes located not far from residential areas, requiring risk assessment for the loss of containment (LoC) event of ammonia. Many studies have modeled ammonia release using ALOHA software but stopped the calculation at the consequence modeling and did not evaluate the risk quantitatively. In this study, a quantitative risk assessment (QRA) was conducted for the LoC of ammonia from the storage tank at PT X, a fertilizer industry in Indonesia, using RISKCURVES software. The scenario and their frequency were chosen based on the Netherlands QRA guidelines. The simulation shows five types of phenomena happening, with toxic dispersion being the most dangerous. Atmospheric conditions influence the toxic dispersion but barely affect the fire and explosion phenomena. Despite the severity of the toxic dispersion, the individual risk calculation shows that the risk in the fertilizer plant area is still acceptable based on the standard of UK HSE.